Calitatea percepută a societăţii româneşti în context european - Mărginean, Ioan (Calitatea Vieții, 2008)
This article is a short version of a presentation given by the author in a bilateral seminar of the Research Institute for Economic Research and Academy of Economic Sciences from Chişinău, in Constanţa, September 2007. The presentation is illustrating the quality of society in Romania from a European perspective. The indicators used are: trust, legitimation of individual actions for success in life, safety in the neighbourhood, quality of social services and social tensions.